Pemilihan Kepala Daerah Secara Tidak Langsung - Mantolongi, Moh. Ismail (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
In 2014, the idea emerged to return regional head elections through the DPRD. However, many parties oppose this idea because it is considered to reduce aspects of democracy. Nevertheless, the idea was eventually regulated in law. The strong rejection from the community prompted the President to issue a government regulation in lieu of law which guarantees that regional head elections will still be carried out directly by the people. In this context, this research formulates several issues, namely the urgency of indirectly electing regional heads and the advantages and disadvantages of the DPRD election system compared to direct election by the people. The method applied in this research is normative research. Based on the author's analysis, there are various arguments and reasons that support the election of regional heads by the DPRD, although there are also weaknesses that can cause dissatisfaction in society.